HIV SERO-PREVALENCE AMONG SUBJECTS WITH THALASSEMIA AT A TERTIARY CARE FACILITY - Balani, Jayant (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: In India, the prevalence of thalassemia trait differs from 3 to 17% in general. HIV can spread to children with thalassemia because they frequently get blood transfusions. Globally, the prevalence of HIV contamination in people with thalassemia differs significantly, ranging from less than 1% to over 20%. The significant sero-prevalence of anti-HIV-1, or 0.5%, in blood donors raises concerned concerns about the danger of HIV transmission during transfusions. Aim and Objectives: to investigate the sero-prevalence of HIV contamination in individuals with thalassemia. Materials and methods: A one-year observational research was conducted in a tertiary care hospital. We took 500 multitransfusion thalassemia subjects who were receiving blood transfusions at the hospital. After obtaining consent, a thorough history was recorded. Five milliliters of blood were aseptically drawn, and HIV testing were carried out in accordance with kit instructions and NACO recommendations. Results: With a male to female proportion of 1.3:1, the age group that predominated was 0–5 years old, with a average age of 9. Of the 500 specimens, 28% had thalassemia intermedia and 72% had thalassemia major. HIV sero-prevalence was 0.4%. Two (1.2%) HIV-positive individuals had received 0–50 blood transfusions and were primarily in the 0–5 age range. Conclusion: Subjects with many blood transfusions for thalassemia frequently have HIV contamination, which is still a serious health issue for them. HIV prevalence may be low since all blood bags must be screened, donors must meet strict selection requirements, sensitive tests are used to screen all blood donors, and public knowledge of HIV is rising. However, newer technologies such as p24 Antigen identification, HIV viral RNA detection by RT-PCR, and HIV Mini pool nucleic acid testing (MP-NAT) can further shorten the HIV window period. Key Words: HIV contamination, Thalassemia.